Swarm‐Derived Indices of Geomagnetic Activity. Issue 11 (18th November 2021) - Papadimitriou, Constantinos; Balasis, Georgios; Boutsi, Adamantia Zoe; Antonopoulou, Alexandra; Moutsiana, Georgia; Daglis, Ioannis A.; Giannakis, Omiros; de Michelis, Paola; Consolini, Giuseppe; Gjerloev, Jesper; Trenchi, Lorenzo
Abstract: Ground‐based indices, such as the Dst, ap, and AE, have been used for decades to describe the interplay of the terrestrial magnetosphere with the solar wind and provide quantifiable indications of the state of geomagnetic activity in general. These indices have been traditionally derived from ground‐based observations from magnetometer stations all around the Earth. In the last 7 years though, the highly successful satellite mission Swarm has provided the scientific community with an abundance of high quality magnetic measurements at Low Earth Orbit, which can be used to produce the space‐based counterparts of these indices, such the Swarm‐Dst, Swarm‐ap, and Swarm‐AE indices. In this work, we present the first results from this endeavor, with comparisons against traditionally used parameters. We postulate on the possible usefulness of these Swarm‐based products for a more accurate monitoring of the dynamics of the magnetosphere and thus, for providing a better diagnosis of space weather conditions. Plain Language Summary: Ground‐based geomagnetic activity indices have been used for decades to monitor the dynamics of the Earth's magnetosphere, and provide information on two major types of space weather phenomena, that is, magnetic storm and magnetospheric substorm occurrence and intensity. This study demonstrates how magnetic field data from a Low Earth Orbit satellite mission, like ESA's Swarm constellation, can be used to derive corresponding space‐based geomagnetic activity indices. Swarm is unraveling one of the most mysterious aspects of our planet: the magnetic field. The magnetic field and electric currents in and around our planet generate complex forces that have immeasurable impact on everyday life. The comparison of Swarm‐based with ground‐based indices shows a very good agreement, indicating that Swarm magnetic field data can be used to provide new satellite‐based global indices to monitor the level of geomagnetic activity. Given the fact that the official ground‐based index for the substorm activity is constructed by data from 12 ground stations solely in the northern hemisphere, it can be said that this index is predominantly northern, while the Swarm‐derived substorm activity index may be more representative of a global state, since it is based on measurements from both hemispheres. Key Points: New geomagnetic activity indices based on Swarm magnetic field data are computed similar to standard ground‐based indices of Dst, ap, and AE Swarm‐derived indices show excellent correlations with both the traditional and SuperMAG‐derived indices Swarm‐based AE index enable us to monitor substorm activity also at the southern hemisphere